Pemanfaatan Pelaporan Keuangan Digital Bagi Perkumpulan Penyelenggara Jasa Boga Indonesia (Ppji) Pekanbaru Dimasa Pandemi Covid-19 - Asepma Hygi Prihastuti; Annesa Adriyani; Suci Ramadhani; Saipul Al Sukri (Asosiasi Dosen Akuntansi Indonesia, 2022)
UMKM are one of the most dominating types of business in Indonesia, but it is undeniable that during the COVID-19 pandemic it was also a business sector that was also affected. The use of digital financial reporting during the COVID-19 pandemic will make it easier for UMKM performers to unify everything that happens in business financial transactions and provide convenience for UMKM performers in conducting financial transactions such as payments, credit, and investments. Digital financial reporting is also used as the basis for tax payments. In addition, digital financial reporting will make it easier for UMKM performers to borrow capital from banks. This service aims to determine the knowledge of UMKM performers who are members of PPJI DPC Pekanbaru so that they can take advantage of financial reporting to support financial activities effectively and efficiently during the COVID-19 pandemic, facilitate the preparation of financial reports, and make it easier for UMKM performers to coordinate with related parties. The results obtained from this digital financial report training, all PPJI DPC Pekanbaru members can apply Si APIK's financial applications well.